Evaluation of the honey and pollen yield of Melipona interrupta bee colonies in the Amazon region - Pires, Adcleia P.; Pacheco, Aline; Martorano, Lucieta G.; Neto, Jonival M.; da Silva Cabral de Moraes, José Reinaldo [UNESP]; de Oliveira Aparecido, Lucas Eduardo [UNESP] (My University, 2020)
The objective of this research was to evaluate the productivity of honey and pollen of Melipona interrupta (Jandaira) colonies during a one-year period. This study was conducted in meliponiculture production colonies located in community of Coroca in the City of Santarem, Para, from October 2016 to December 2017. All collections of meliponiculture material were conducted during the first week of each month. Characteristics such as the total number of food pots, height, diameter, and volume of honey and pollen pots, the mass of the colony, production of pollen and honey, and the productivity of the bee colony as a whole were constantly monitored. Each month, biometric measurements of fifteen colonies of native bees of the specie were conducted and analyzed in the Statistical Analysis System. The greatest honey production by these colonies was strongly correlated with the less-rainy period that occurs in the region, and this production was most pronounced during October through December.
Keywords: Bees; Brazil; Community; Meliponiculture